Anti-money laundering and counter-terrorism financing survey of regulated businesses in Australia - methodology report - Adele Eliseo
This report provides a stand-alone description of how the Australian Institute of Criminology’s Anti-money Laundering/Counter-terrorism Financing Survey of regulated businesses was undertaken, emphasising the importance of understanding the methodology and design of this national census of regulated businesses in Australia. As is often the case with social scientific research of a quantitative nature, the detail of how surveys were conducted are sometimes relegated to deep within a long report, or attached in a lengthy appendix, often being overlooked by the average reader. This report provides a stand-alone description of how the Australian Institute of Criminology’s Anti-money Laundering/Counter-terrorism Financing Survey of regulated businesses was undertaken, thus emphasising the importance of understanding the methodology and design of this national census of regulated businesses in Australia. It reviews all of the procedures and steps undertaken from a data collection and methodological perspective and provides an important accompaniment to the major survey report published in conjunction with this methodological review. Both reports should be read together. The current report provides a summary of the methodological approach, consolidation of assorted reports generated throughout the study, a review of sample utilisation and response dynamics and a summary of issues for consideration for future similar surveys